2020
DOI: 10.1177/1756284820924194
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-associated liver injury in colorectal cancer

Abstract: Patients with colorectal cancer (CRC) have benefited significantly from advances in multimodal treatment with significant improvements in long-term survival. More patients are currently being treated with surgical resection or ablation following neoadjuvant or adjuvant chemotherapy. However, several cytotoxic agents that are administered routinely have been linked to liver toxicities that impair liver function and regeneration. Recognition of chemotherapy-related liver toxicity emphasizes the importance of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Nevertheless, to circumvent possible limitations and/or misleading results unforeseen by us from the LDH assay with normal, non-transformed cells (HUVECs and colon epithelial cells), as such as undetected early induced death (occurring outside the experimental time point evaluated by us) or by eventual LDH degradation in the media of these cells, we decided to assess whether normal colon mucosal organoids would tolerate KAN0438757 treatment. The striking results obtained with intestinal PDOs further supported the idea that KAN0438757 could possibly target tumor cells preserving normal tissues, a very desired scenario in oncological therapeutical approaches, where severe systemic toxicity affects patients’ outcomes [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, to circumvent possible limitations and/or misleading results unforeseen by us from the LDH assay with normal, non-transformed cells (HUVECs and colon epithelial cells), as such as undetected early induced death (occurring outside the experimental time point evaluated by us) or by eventual LDH degradation in the media of these cells, we decided to assess whether normal colon mucosal organoids would tolerate KAN0438757 treatment. The striking results obtained with intestinal PDOs further supported the idea that KAN0438757 could possibly target tumor cells preserving normal tissues, a very desired scenario in oncological therapeutical approaches, where severe systemic toxicity affects patients’ outcomes [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 81%
“…However, there has yet to be a clear consensus regarding the effect of oxaliplatin on steatosis, especially in light of findings such as that of Lu and colleagues, who showed that oxaliplatin aggravates existing steatosis in a non-alcoholic fatty liver disease mouse model [27]. More widely accepted is the association of CASH with irinotecan-based chemotherapies, which were not explored in the present study but would be highly pertinent for future investigations [28].…”
Section: Discussionmentioning
confidence: 82%
“…This may trigger an inflammatory reaction leading to steatohepatitis, and in turn to fibrosis and cirrhosis. Sinusoidal obstruction syndrome is a separate entity with direct toxicity to LSEC leading to occlusive phenomena in the sinusoids[ 407 ].…”
Section: Section 8: Liver Regeneration: Implications For Therapy Of Liver Tumoursmentioning
confidence: 99%